Faktor-Faktor Kepuasan Kerja Perawat di Rumah Sakit Swasta Kota Padang Indonesia - Conny Oktizulvia; Sari Indah Kesuma (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
Nurses’ job satisfaction is still becoming an important issue because it is not only closely related to high turnover rates, work stress and burnout, but also closely related to service and patient satisfaction in the hospital. This study aimed to analyze nurses’ job satisfaction factors and dominant factors influencing it among nurses in private hospitals in Padang Indonesia. A cross sectional, correlational design was used. Data were collected by questionnaire and proportional random sampling of 189 nurses in three hospitals was conducted. Data collected used questionnaire consisting of sociodemographic and the Job Satisfaction Survey (JSS). Descriptive statistics, correlation, and multiple linear regression analyses were used to examine the data. The average of job satisfaction was found at 73.5% of nurses satisfied with their job. Nature of work, co-worker, pay, and fringe benefits were the most significant factors influence toward nurses’ job satisfaction. The results can be used as a basis for evaluation, early detection, and future planning for nursing managers and management. Results also highlight the need to emphasize positive factors to upgrade nature of work, positive co-worker relationships, pay, and fringe benefits to achieve an excellent service quality by nurses.